Peran Dinas Perpustakaan Dan Kearsipan Kabupaten Labuhanbatu Selatan dalam implementasi sustainable devolepment goals - Sindi Aulia Nasution; Retno Sayekti (S1 Ilmu Perpustakaan dan Informasi Islam FTK UIN Antasari Banjarmasin, 2023)
The Library and Archives Service of South Labuhanbatu Regency is an agency implementing local government affairs in the field of libraries and archives. The purpose of this research is to find out the various efforts of the South Labuhanbatu Regency Library and Archives Service in implementing work programs that are in line with the SDGs. This study uses data collection techniques through observation, interviews, and documentation. In this study, researchers used a data validity test through data triangulation. The data analysis used refers to the Miles and Huberman model. In this study there were 4 people as informants, consisting of librarians at the Library and Archives Service of South Labuhanbatu Regency. Based on the research that has been carried out, it can be concluded that the Library and Archives Service of Labuhanbatu Selatan Regency has an important role in supporting the SDGs, especially in pillars 1 and 4, namely poverty alleviation and delivery of quality education. The results of this research can be used by libraries to develop information services that support the SDGs.